The Development of Interactive Media in Economics for Senior High Schools Students Using Android Platform - Mohamad Arief Rafsanjani; Dhiah Fitrayati; Muhammad Abdul Ghofur; Eka Hendi Andriansyah; Albrian Fiky Prakoso (Universitas Negeri Malang, 2021)
This study aims to determine the feasibility, practicality, and effectiveness of developing interactive media for economic subjects with the Android platform. This study followed the development research using the 4D model consisting of four stages: defining, designing, developing, and disseminating. The trial subjects used class X SMA Lab school Universitas Negeri Surabaya. The instruments were validated by undergoing sheets and questionnaires. The collected data were further analyzed with descriptive analysis by validating material experts, media experts, practitioners, and students’ responses. The findings indicate that the review and validation by a presentation expert showed a validation score of 85.19%. The number of students who have test scores above 78 is 26 out of 30 students. Therefore, the classical completeness obtained is 86.67%. Based on these results, it can be concluded that Android-based interactive media for economics class X is feasible, practical, and effective in improving student learning outcomes. Keywords: Android platform, Economics subject, Interactive media, Senior high schools